Experimental Study On The Use Of Ejector With Two-Evaporator Temperatures Applied For Performance Enhancement Of Split Type AC System - Arsana, Made Ery (International Journal of Engineering and Emerging Technology; Vol 2 No 2 (2017): July - December, 2018)
The study was focused on the performance of a modified split type air conditioning (AC) system that used an ejector as its expansion device. The purpose of this study was to demonstrate that replacement of accumulator device with secondary evaporator of a standard air conditioning ejector system could improve coefficient of performance (COP) of the system. The tested split air conditioning system was a non-inverter system charged with R290 refrigerant. The evaporator of the system was placed in a test chamber incorporated with electric air heater to maintain constant load to the system. The results showed that the modified ejector AC system utilizing secondary evaporator could provide significant COP enhancement of about 13% over that of the standard ejector AC system.   Keywords: two evaporator temperature ejector system, COP enhancement, and split type AC system